Mechanism on emulsified vegetable oil stimulating nitrobenzene degradation coupled with dissimilatory iron reduction in aquifer media. (July 2018) - Chi, Zifang; Lei, Jiansen; Ding, Linjie; Dong, Jun
Graphical abstract: Highlights: EVO stimulates NB degradation coupled with dissimilatory iron reduction. EVO increases the bioavailable iron content in natural mineral. The mechanism and reaction process were speculated. Abstract: Microbial dissimilatory iron reduction could remediate reducible pollutants in groundwater, such as nitrobenzene (NB). But the natural attenuation rate in aquifer is limited. To stimulate this process, emulsified vegetable oil (EVO) was injected as a remediation agent. The mechanism of this process was studied. Results showed that the addition of EVO made iron easier used by microorganisms and thus promoted dissimilatory iron reduction. The readily used Fe(III) served as electron acceptor and was reduced to Fe(II). Fe(II) supplied electrons to NB, with NB reduced to aniline. Sulphide in the aquifer media also donated electrons and oxidized to polysulfide, then forming precipitates with Fe(II) to the surface of aquifer media, and thus slowing down the electron supplying of EVO and forming permanent efficiency for NB remediation. The work helps to complete a systematic understanding of NB remediation process under stimulation of EVO.